English in medicine : a course in communication skills / Eric H Glendinning, Beverly A S Holmström - Glendinning, Eric H.
This book aims to help you communicate in English with patients and their relatives, with medical colleagues, and paramedical staff. It is designed to help you cope with medical reading of all kinds, from documents to journal articles. Students should find this book useful in the clinical phase of studies, and the section on reading skills should help with textbooks. The authors have cooperated closely with members of the medical profession, and have experience helping overseas medical personnel with their communicative needs